A new species of Xestophrys Redtenbacher, 1891 (Orthoptera: Tettigoniidae; Conocephalinae; Copiphorini) from India - Kumar, Hirdesh; Chandra, Kailash; Saini, Jagdish (Zootaxa, 2019)
In the present paper a new species, Xestophrys namtseringa Kumar & Chandra sp. nov. is described and illustrated from Indian Himalaya. Key to all the known species of Xestophrys Redtenbacher, 1891 is also provided. [Zoobank URL: urn:lsid:zoobank.org:act:C18B59A4-30F8-4753-8739-6482D7F5A6B2]